Domestic violence and its relationship with quality of life in pregnant women during the outbreak of COVID-19 disease - Somayyeh Naghizadeh; Mojgan Mirghafourvand; Roghaye Mohammadirad (BMC, 2021)
Abstract Background During the COVID-19 pandemic, pregnant women bear considerable physical and psychological stress because of their special conditions, which combined with other stress factors such as violence, makes their situation even more critical. This study aimed to investigate the prevalence of domestic violence and its relationship with quality of life in pregnant women during the COVID-19 pandemic. Methods This cross-sectional study was performed with the participation of 250 pregnant women in the obstetrics clinic of 29-Bahman Hospital, Tabriz city. Using a three-part questionnaire consisting of the socio-demographic and obstetrics information, the domestic violence questionnaire developed by WHO, and the SF-12 quality of life questionnaire, the required information was collected. A general linear model was then used to determine the relationship between domestic violence and quality of life, while adjusting the socio-demographic and obstetrics information. Results According to the data, more than one-third of pregnant women (35.2 %) had experienced domestic violence. The most common type of violence experienced was emotional violence (32.8 %), followed by sexual violence (12.4 %), and physical violence (4.8 %). The mean score of the physical health department of quality of life in the group of women exposed to violence (50.21) was lower compared to the unexposed group (53.45), though there was no significant difference between them (P = 0.25). However, the mean score of the mental health department of quality of life in women exposed to violence (46.27) was significantly lower compared to unexposed women (61.17) (P < 0.001). Based on the general linear model, the mean score for quality of life in the mental health dimension was significantly higher among unexposed women compared to those exposed to violence (β = 9.3, 95 %CI: 3.5 to 15.0, P = 0.002). Conclusions The findings of this study indicate a high prevalence of domestic violence and its relationship with a low quality of life during the COVID-19 pandemic. Therefore, the findings signify the importance of screening pregnant women in terms of domestic violence in respective centers as well as the necessity of conducting proper interventions to address domestic violence to improve the quality of life in women.